2007
DOI: 10.1167/iovs.07-0356
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity against Ocular Herpes Infection and Disease Induced by Highly Immunogenic Self-Adjuvanting Glycoprotein D Lipopeptide Vaccines

Abstract: Vaccination with a mixture self-adjuvanting lipopeptides containing novel HSV-1 immunodominant gD T-cell epitopes protected mice from ocular herpes infection and disease. The strength of protective immunity induced by these lipopeptides together with their safety provide a molecularly defined vaccine formulation that could combat ocular herpes infection and disease in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 68 publications
(115 reference statements)
0
42
0
1
Order By: Relevance
“…Heat-inactivated virus was made by heating a virus solution at 100°C for 5 min. HSV inactivation was confirmed by the inability to produce plaques when tested on Vero cells as previously described (11,52).…”
Section: Study Population From August 2003 To October 2007 We Screementioning
confidence: 99%
“…Heat-inactivated virus was made by heating a virus solution at 100°C for 5 min. HSV inactivation was confirmed by the inability to produce plaques when tested on Vero cells as previously described (11,52).…”
Section: Study Population From August 2003 To October 2007 We Screementioning
confidence: 99%
“…Conformational analysis of the gD 301-309 sequence confirmed the presence of a type I β-turn structure, which included the aspartate-proline-valine-glycine (DPVG) epitope core. 33 Moreover, previous studies indicated that the gD 301-309 epitope induced gD-specific responses and also elicited an immune response that conferred protection against lethal HSV-1 infection. 34 ).…”
Section: Identification Of Peptide Epitopesmentioning
confidence: 99%
“…But the strength of this protective immunity induced by these lipopeptides together with their safety need to be ascertained to combat ocular herpes infection and disease in humans [58].…”
Section: Recent Developments: Newer Drug Formulations and Vaccinationmentioning
confidence: 99%